The IMF's Role in Low-Income Countries : Issues and Challenges - Lombardi, Domenico (IMF Working Papers; Working Paper ;, 2005)
Drawing on recent research, this study elaborates on the role of the IMF in support of its lowincome members, pointing to the global character of the institution and to its superior ability-given its multilateral nature-to serve as a financial institution, an information provider, and a commitment device. The IMF assists low-income members through a range of activities that are normally bundled together, including lending, offering policy advice, and providing assistance with capacity building. The study reviews the features of IMF policies towards its low-income membership and points to the main challenges to their success.